A new simple technique for development of seedling infection of white rust of rapeseed-mustard from oospores of Albugo candida - and S.R. RIMMER3, S.J. KOLTE1, J.N. SACHAN2 (Indian Phytopathology, 2002)
The fully ripe stagheads as produced on naturally infected plants of Brassica juncea cv. Varuna and B. campestris var. toria cv. PT 303 were collected separately from the above 2 crop species grown in isolation as seed crops at Pantnagar, Uttar Pradesh, India. The stagheads were then ground separately using a Waring Blender and the grindings were screened through a 60-mesh sieve to get a brown powder containing a large number of oospores. Seeds of the susceptible B. juncea cv. Varuna and B. campestris var. toria cv. PT 303 were surface sterilized with sodium hypochlorite and about 5-7 g of oospore powder was added separately into each of the 2 seed lots. Glass distilled sterile water was then added to wet the contents allowing an excess of water for seed soaking for 12 h. After soaking the leachate was removed by vacuum filtration and the seeds were dried before sowing in pots. The results showed that both the cultivars displayed more than 95% emergence. The white rust symptoms appeared on the cotyledons of Varuna and PT 303 in about 13-15 days after sowing. In about 20 days, all the infected seedlings showed distinctive symptoms. The white rust pustules on cotyledons of Indian mustard cv. Varuna were quite conspicuous and well formed compared with those on cotyledons of rape/toria cv. PT 303. The average % of cotyledonary infected plants for Indian mustard was 79.51 but for rape/toria it was only 4-12%. About 2-15% of infected Indian mustard plants showed systemic infection, whereas, infectedrape/toria plants did not show systemic infection. These results suggest that the A. candida race which infects Indian mustard is more virulent than the A. candida race which infects rape/toria.